Vulvar Cancer in the North of Israel - Orit Kaidar-Person; Nour Ibrahim; Amnon Amit; Roxolyana Bortnyak-Abdah (Rambam Maimonides Medical Journal, 2014)
Purpose: This is a population study of patients who were treated for vulvar cancer in a tertiary center in northern Israel, aimed to report clinical findings, treatment, and outcome.